Detection and classification of single-circuit and intra-circuit faults based on analysis of current signals of near-end terminal in double-circuit transmission lines - Mahyar Abasi; Pirooz Gorjian (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
This paper presents a method of inter-circuit and intra-circuit fault detection in a double-circuit transmission line based on the analysis of six-phase current signals of a single terminal. The method is developed by analyzing the output results of several mathematical integral transforms, including the modified Stockwell, Hilbert, and modal transforms. The algorithm is designed in three steps. In the first step, by investigating the alpha component of the modal transform, it can be recognized that the fault is single-circuit or double-circuit. Then, in the second step, by analyzing the zero component of the modal transform, it can be identified if the fault is grounded or not. In the third step, by using the analysis of a new index based on the combination of modified Stockwell and Hilbert transforms and a statistical index based on correlation, the faulty phase of the double-circuit line can be identified. The method is coded in the MATLAB environment and the test network is modeled in MATLAB/Simulink. The implementation results of different fault scenarios as well as the analysis of the algorithm's behavior under critical conditions validates the algorithm's high performance.